Study On The Growth, Yield And Yield Attributes Of Eight Varieties Of Bitter Gourd (Momordica Charantia L.) (Chittagong University Journal of Biological Sciences, 2024)
Seeds of eight varieties of  bitter gourd (V1, V2, V4, V5, V6, V7, V9 and V10) were sown in the experimental field and their growth, yield and yield attributes were studied. The length, number of nodes and leaves and number of  branches per plant were highest in V1. The number of female flowers, number of fruits and yield per plant were found maximum in V4. Chlorophyll a and total pigment contents of  leaves were highest in V2. Total NPK and Vitamin C contents of fruits were found highest in V6.The Chittagong Univ. J. B. Sci.,Vol. 7(1 &2):167-174 , 2012